The last 750 ka in loess–palaeosol sequences from northern France: environmental background and dating of the western European Palaeolithic. (9th March 2021) - Antoine, Pierre; Coutard, Sylvie; Bahain, Jean‐Jacques; Locht, Jean‐Luc; Hérisson, David; Goval, Emilie
ABSTRACT: This study presents an overview of Middle Pleistocene loess–palaeosol sequences (LPS) in northern France and discusses the palaeoclimatic significance of the pedosedimentary record in the context of western European LPS and of global climatic cycles for the last 750 ka. In this area, the oldest loess deposits (early Middle Pleistocene) are preserved in sedimentary traps (leeward scarps of fluvial terraces and dissolution sinkholes). They result from local deflation processes reworking Pleistocene sandy fluvial deposits or relicts of Tertiary sands. A large extension of typical calcareous loess over the landscape, the Loess Revolution, is then observed during MIS 6, with heavy mineral assemblages testifying to long‐distance transport from the polar desert area of the dried eastern Channel. A correlation scheme is proposed between the global records of northern France in continental environments and both global palaeoclimatic records and other main western European LPS. After 30 years of research, northern France LPS stand as a fundamental archive of the impact of interglacial–glacial climatic cycles as well as millennial events. Finally, these works provide a robust chronoclimatic framework for the study of the western European Late Acheulean and Middle Palaeolithic and for the relative dating of the various fluvial terraces that they fossilise.